1995
DOI: 10.1021/np50122a022
|View full text |Cite
|
Sign up to set email alerts
|

Polycerasoidin and Polycerasoidol, Two New Prenylated Benzopyran Derivatives from Polyalthia cerasoides

Abstract: Two novel metabolites of mixed biogenesis, polycerasoidin [1] and polycerasoidol [2], have been isolated from the stem bark of Polyalthia cerasoides. Their structures were established on the basis of nmr spectroscopic techniques, including 2D correlated nmr spectroscopy (COSY 45, HMQC, and HMBC).The genus Polyalthia includes more than 150 species of trees belonging to the family Annonaceae. It is considered one

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 20 publications
2
39
0
Order By: Relevance
“…They were identified as oligandrol (2) (Banfield et al 1994), (6E,10E)-isopolycerasoidol (3) (Gonzalez et al 1996) and polycerasoidol (4) (Gonzalez et al 1995). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were identified as oligandrol (2) (Banfield et al 1994), (6E,10E)-isopolycerasoidol (3) (Gonzalez et al 1996) and polycerasoidol (4) (Gonzalez et al 1995). …”
Section: Resultsmentioning
confidence: 99%
“…is a species of trees, mainly distributed in Southeast Asia. In this work, a new benzopyran derivative, pseudindochin (1), and three known compounds, oligandrol (2) (Banfield et al 1994), (6E,10E)-isopolycerasoidol (3) (Gonzalez et al 1996) and polycerasoidol (4) (Gonzalez et al 1995), were isolated from the 95% EtOH extracts of the twigs and leaves of P. indochinensis, which were collected from the Yunnan Province of China. In this paper, we describe the isolation, structural elucidation and cytotoxic activities of the compounds isolated from P. indochinensis.…”
Section: Introductionmentioning
confidence: 99%
“…The on-flow LC-1 H-NMR of the second antioxidant compound 7 exhibited three singlet signals owing to methyl groups, two aromatic protons, two olefinic protons and eight aliphatic protons. With these on-line data, it was difficult to suggest a possible structure for 7; however, a cross check of its molecular weight (358) with all known constituents of the Annonaceae family in a database of natural products suggested that 7 might be polycerasoidol, a tocopherol derivative isolated from Polyalthia cerasoides (Annonaceae) (Gonzalez et al, 1995). The 1 H-NMR of polycerasoidol was comparable to the on-flow 1 H-NMR of 7, however, the chemical shifts of the on-flow 1 H-NMR of 7 between 1.90 and 2.10 ppm were not visible due to their location under the suppressed peaks of the LC-solvent system (acetonitrile; 1.90-2.10 ppm).…”
Section: On Flow Analysis Of Crude Extractsmentioning
confidence: 99%
“…With these on-line data, it was difficult to make any suggestion for the possible structure of 8. However, a cross-check of its molecular weight (MW: 358 Da) with all known constituents of the Annonaceae family in a database of natural products suggested 8 to be polycerasoidol, a tocopherol derivative isolated from Polyalthia cerasoides (Annonaceae) (Gonzalez et al, 1995). The 1 H-NMR of polycerasoidol was comparable to the on-flow 1 H-NMR of 8, however, the chemical shifts between 1.90 and 2.10 ppm were not visible due to their location under the suppressed peaks of the LC-solvent system (MeCN, d 1.90-2.10).…”
Section: Combination Of Lc/ms and Lc/nmr With On-line Assays For The mentioning
confidence: 99%